Manajemen Risiko Operasional pada Apotek di Kabupaten Brebes - Tiara Amanda Rosmalia; Amirah Amirah (AKUNTANSI 45, 2026)
This study aims to identify, analyze, and evaluate operational risks in pharmacies in Brebes Regency and assess the effectiveness of mitigation efforts that have been implemented. The study used a quantitative survey method with a questionnaire to 20 pharmacies that were selected purposively. The analysis is carried out based on the risk management framework, including identification, analysis, evaluation, and handling of risks. The results of the study showed that most of the operational risks were in the low to medium category, such as medication delivery errors and drugs close to expiration with an average value of 1.5 as well as the risk of long queues, stock shortages, equipment damage, and reputation decline with a value of 1.9-2.3. On the other hand, the implementation of risk control has gone quite well, as can be seen from the high average value (3.3-3.9) in mitigation aspects, such as the implementation of FEFO, double prescription checking, internal audit, the use of CCTV, and written SOPs, overall, pharmacies in Brebes district have a fairly effective risk management system, although there are still improvements in the risk identification and documentation process to strengthen risk management in a sustainable manner.